Development of molecular markers for anthracnose resistance in vegetable cowpea [vigna unguiculata (L.) walp] - Dolagobinda Pradhan (Centre for plant biotechnology and molecular biology, College of horticulture, 2015)
Cowpea is one of the most important food legume crops in the semi-arid tropics, covering Asia, Africa, Southern Europe and Central and South America. Nigeria is the centre of origin for cowpea and in India, it is exclusively known as a kharif season pulse but the demand of cowpea as vegetable is increasing. In India, cowpea is grown in about 0.5 million ha but productivity is as low as 600-750 kg grains ha-1. All the pole type vegetable cultivars are highly susceptible to anthracnose caused by Colletotrichum lindemuthianum, which is the most destructive disease, not only for cowpea but also in other legumes. Since no effective measures are capable to manage this disease, the losses can be up to 74-100 per cent and hence breeding the resistant cultivars is suggested as the only promising strategy. Molecular marker assisted selection offers precision in the breeding process but so far no markers are identified in this crop for the anthracnose resistance gene. With this background, the study on “Development of molecular markers for anthracnose resistance in vegetable cowpea [Vignaunguiculata (L.) Walp.]” was carried out at Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, during August 2013 to June 2015. The objective of the study was to identify an ISSR or RAPD molecular marker linked with anthracnose disease resistance in vegetable cowpea, using bulked segregant analysis to enable marker assisted selection. The dual purpose semi-trailing cultivar Kanakamony, which is reported as immune to anthracnose and the high yielding trailing vegetable type cultivar Sharika, which is susceptible, were used for the development of the mapping population for BSA to identify the marker. The parental populations were grown in separate fields in the month of October 2014 as per the package and practices recommended from KAU. Controlled crosses were made to develop F1 seeds during November and December months. Thirty F1 plants were grown during January - March 2015 and the F2 seeds were developed through selfing. The F2 segregating progenies were raised during May-June, in the pots and maintained in greenhouse. Evaluation of parents with F1 of Sharika × Kanakamony and reciprocal cross for morphological characters revealed that pole type and black seed colour characters of Sharika were dominant over semi-trialing and red colour seed of Kanakamony. To isolate the fungal spores for artificial inoculation on the F2 plants, infected plant parts were collected and initially cultured in 3 different media viz. PDA, NGA and CDA. NGA and PDA medium were selected for artificial inoculation based on the characteristics of fungal spores. Artificial inoculation was initially done on 15 days old seedlings and was repeated after 15 days with an approximate concentration of 106 spores/ml and the highly resistant and susceptible F2 plants were identified for BSA. Good quality DNA was isolated from the parents and 47 RAPD and 43 ISSR primers were screened for their capability to generate polymorphic bands. Subsequently, based on the initial screening, 12 RAPD and 10 ISSR primers were selected for bulk segregant analysis. The bulked segregant analysis was done using the DNA from the resistant parent, susceptible parent, resistant F2 bulk and susceptible F2 bulk. BSA with the RAPD primer OPA 02 revealed a polymorphic band at 850 bp which was present in the susceptible parent and susceptible bulk and absent in the resistant parent and bulk. BSA with ISSR primers UBC 810 and UBC 811 produced polymorphic bands at 1.4 kb and 1.5 kb, respectively, which were present in resistant parent and resistant bulks. The co-segregation analysis has to be performed, the marker has to be characterized and validated for the use in breeding programmes.